MEASUREMENT OF THE PROPERTIES OF SAND IN A CALIBRATION CHAMBER BY THE CONE PRESSUREMETER TEST - Schnaid, F; Houlsby, G (1992)
The cone pressuremeter is a new site investigation device which incorporates a pressuremeter behind a standard cone penetrometer tip. A series of calibration chamber tests is described, in which three cone pressuremeter prototypes of different cross-sectional areas were used. A programme of calibration designed to examine the influence of relative density, stress level and stress ratio on the values of limit pressure obtained from the cone pressuremeter test and the cone resistance values obtained from the cone test is presented. A procedure for deducing the in situ horizontal stress, density and friction angle is described, and is used to back-analyse the test data. -from Authors